Reporting adverse drug reactions: Definitions of terms and criteria for their use
Term. Musculo-Skeletal system disorders(SOC 0200). Liver and biliary system disorders. Metabolic and nutritional disorders. Platelet, bleeding and Clotting disorders. Urinary system disorders. Body as a whole.